Attributional consensus: The importance of agreement over causes for team performance to interpersonal outcomes and performance. (July 2019) - Murray, Ross M.; Coffee, Pete; Eklund, Robert C.; Arthur, Calum A.
Abstract: Objectives: Investigate (a) the effects of attributional consensus on interpersonal outcomes and performance, (b) the effects of attribution type (i.e., adaptive/maladaptive) on performance, and (c) the interaction effects between attributional consensus and attribution type on performance. Design: Across two studies (i.e., vignette and behavioural experiments), independent samples t-tests were used to examine the main effects of attributional consensus on interpersonal outcomes. A 2 (attributional consensus: high, low) x 2 (attribution type: adaptive, maladaptive) x 2 (time: pre, post) ANOVA with repeated measures on the last factor was used to analyse the main and interaction effects of attributional consensus and attribution type on performance. Method: In Study 1, participants ( N = 100) read a vignette describing a hypothetical situation in which they and their partner agreed or disagreed over an adaptive or maladaptive attribution. They then completed measures of conflict and cohesion. In Study 2, participants ( N = 56) completed an experiment in which they performed a dart throwing task with a partner (a confederate) and were subsequently told they failed the task. After selecting an adaptive or maladaptive attribution, the confederate then agreed or disagreed with the participant. Measures of conflict, cohesion, social identity, and performance were then taken. Results: High attributional consensus led to lower levels of conflict and higher levels of cohesion and social identity. Further, regardless of attribution type, high attributional consensus led to better performance. Conclusion: Overall the results provide evidence for the positive effects of high attributional consensus on interpersonal and performance outcomes. Highlights: High attributional consensus between teammates positively affects team dynamics. High attributional consensus between teammates positively affects performance. Attributional consensus may be more important than attributional content.